ANALISIS KEPUASAN KONSUMEN TERHADAP KUALITAS PELAYANAN AGROWISATA KOPI KARANGANYAR KABUPATEN BLITAR (Studi Kasus di Kelurahan Karangannyar, Kecamatan Nglegok, Kabupaten Blitar) - Pratiwi, Rika; Wahyu Budiman, Eko; Widiatmanta , Jeka (grafting, 2022)
The purpose of this study is to find out the services provided by Karanganyar Coffee Agrotourism, find out the level of consumer satisfaction with the quality of Karanganyar Coffee Agrotourism services and know the impact of service quality on visitor satisfaction of Karanganyar Coffee Agrotourism. The results of the research on the level of customer satisfaction with the service of the karanganjar coffee shop are very satisfying, we can draw such conclusions because we see from the results of the distribution of quisoners that have been distributed to visitors in the karanganjar coffee shop. Visitors to the karanganjar coffee shop gave a very satisfied assessment of the level of service in the karanganjar coffee shop and karanganjar coffee agrotourism. According to the visitors, giving a very satisfied value is a very suitable assessment given, looking at the level of service that has been provided by employees and baristas who are very responsive and dexterous